Risk of astrocytic brain tumors associated with occupational chemical exposures. A case-referent study. - Thomas, Terry L.; Stewart, Patricia A.; Stemhagen, A.; Correa, P.; Norman, S. A.; Bleecker, M. L.; Hoover, R. N. (Scandinavian Journal of Work, Environment & Health, 1987)
A case-referent study was conducted on the risk of brain tumors among workers exposed to organic chemicals in petroleum refining and chemical manufacturing. Brain tumor cases in northern New Jersey, Philadelphia, and the Gulf Coast of Louisiana were identified from death certificates of a recent three-year period. The cases (N = 300) were white men aged greater than or equal to 30 years with a confirmed diagnosis of glioblastoma multiforme, astrocytoma, or a mixed glioma with astrocytic cells. The referents (N = 386) were white men who died from causes other than brain tumor, epilepsy, cerebrovascular disease, suicide, or homicide and were frequency-matched with the cases on age at death, year of death, and study area. Next-of-kin were interviewed for complete occupational histories. No statistically significantly elevated odds ratios (OR) were associated with employment in the chemical industry. The risk of astrocytic tumors was elevated among the subjects with production or maintenance jobs in petroleum refining (OR 1.7, 95% confidence interval 0.7-4.2); however, it decreased with duration employed. There were nonsignificant excess risks of astrocytic tumors among the men exposed to cutting fluids (OR 1.6) or organic solvents (OR 1.3), and also among the subjects exposed to lubricating oils (OR 1.4), organic solvents (OR 1.5), or cutting fluids (OR 1.8) for greater than or equal to 20 years.